Infrared Spectroscopy Elucidates the Inhibitor Binding Sites in a Metal‐Dependent Formate Dehydrogenase. Issue 54 (3rd August 2022) - Laun, Konstantin; Duffus, Benjamin R.; Wahlefeld, Stefan; Katz, Sagie; Belger, Dennis; Hildebrandt, Peter; Mroginski, Maria Andrea; Leimkühler, Silke; Zebger, Ingo
Abstract: Biological carbon dioxide (CO2 ) reduction is an important step by which organisms form valuable energy‐richer molecules required for further metabolic processes. The Mo‐dependent formate dehydrogenase (FDH) from Rhodobacter capsulatus catalyzes reversible formate oxidation to CO2 at a bis‐molybdopterin guanine dinucleotide (bis‐MGD) cofactor. To elucidate potential substrate binding sites relevant for the mechanism, we studied herein the interaction with the inhibitory molecules azide and cyanate, which are isoelectronic to CO2 and charged as formate. We employed infrared (IR) spectroscopy in combination with density functional theory (DFT) and inhibition kinetics. One distinct inhibitory molecule was found to bind to either a non‐competitive or a competitive binding site in the secondary coordination sphere of the active site. Site‐directed mutagenesis of key amino acid residues in the vicinity of the bis‐MGD cofactor revealed changes in both non‐competitive and competitive binding, whereby the inhibitor is in case of the latter interaction presumably bound between the cofactor and the adjacent Arg587. Abstract : Metal‐dependent formate dehydrogenases (FDH) are capable of oxidizing formate to CO2 reversibly. Here, we compared IR spectroscopic data with DFT calculations and inhibition kinetics to study the putative binding mode of CO2 /formate at the bis‐MGD cofactor with the help of isoelectronic and charged product analogues. Experimental and theoretical data exclude a direct binding of the inhibitor molecules to the bis‐MGD.